Effect of platele-rich plasma on healing of class III furcation defects treated with autogenous bone grafting and guided tissue regeneration: a histomorphometric sutdy in dogs - Fernandes, José Marcos Alves [UNESP]; Silva, Emilio Barbosa e [UNESP]; Rêgo, Rodrgio Otávio Citó César [UNESP]; Molon, Rafael Scaf de [UNESP]; Zandim-Barcelos, Daniela Leal [UNESP]; Spolidório, Luís Carlos [UNESP]; Cirelli, Joni Augusto [UNESP] (My University, 2011)
Objective: The purpose of this study was to evaluate the effects of the platelet-rich plasma (PRP) when used in combination with autogenous bone graft and bioabsorbable membrane (Resolut® ) in the treatment of Class  III furcation defects in dogs. Material and method: Class III furcation defects (5 mm in height and in depth) were surgically created in the mandibular third premolars of five mongrel dogs. After nine weeks, the lesions were treated with scaling and root planning and each defect received one of the following treatments: autogenous bone graft + membrane (group C) or PRP + autogenous bone graft + membrane (group T). After a healing period of 90 days, the animals were sacrificed. Routine histological processing and staining with hematoxilyn and eosin and Masson trichrome were performed and a histomorphometric analysis determined the effect of the treatments on periodontal tissue regereneration. Data were analyzed by Hotelling’s T-squared (p < 0.05). Result: No statistically significant difference between C and T groups was observed by the histomorphometric analysis of the furcation area. Both treatment groups demonstrated similar regenerative results with the furcation defects partially filled and periodontal regeneration limited to the experimental notches of the lesions. (p > 0.05). Conclusion: According to the present results, PRP does not enhance the periodontal regeneration in class III furcation defects treated with autogenous bone graft and bioabsorbable membrane.

Objetivo: O objetivo deste estudo foi avaliar histologicamente os efeitos do plasma rico em plaquetas (PRP), quando usado em combinação com enxerto ósseo autógeno e membrana bioabsorvível (Resolut® ) no tratamento de defeitos de furca Classe III em cães. Material e método: Cinco cães foram usados neste estudo. Defeitos de furca classe III (5  mm de altura e de profundidade) foram criados cirurgicamente no terceiro pré-molar inferior de ambos os lados. Nove semanas após a primeira cirurgia, os terceiros pré-molares foram tratados com raspagem e alisamento radicular e cada defeito recebeu um dos seguintes tratamentos: Enxerto ósseo autógeno + membrana (grupo C) ou PRP + enxerto ósseo autógeno + membrana (grupo T). Após um período de cicatrização de 90 dias, os animais foram sacrificados. Processamento histológico de rotina e coloração com hematoxilina e eosina e tricrômico de Masson foram realizados para determinar o efeito dos tratamentos na regeneração dos tecidos periodontais. Os dados foram analisados pelo teste T2 de Hotelling (p  <  0,05). Resultado: A análise histomorfométrica da área de furca não mostrou nenhuma diferença estatisticamente significativa entre os grupos C e T. Os dois grupos de tratamento demonstraram resultados regenerativos semelhantes, com os defeitos de furca parcialmente preenchidos e a regeneração periodontal foi limitada à marca experimental apical das lesões. (p > 0,05). Conclusão: Dentro dos limites deste estudo, concluiu-se que o uso de PRP não melhorou a regeneração periodontal em defeitos de furca classe III tratados com enxerto ósseo autógeno e membrana bioabsorvível.
Efeito do plasma rico em plaquetas na reparação de lesões de furca classe III tratadas com enxerto ósseo autógeno e regeneração tecidual guiada: estudo histomorfométrico em cães
Keywords: Furcation defects; Platelets-rich plasma; Guided tissue regeneration; Absorbable membrane; Defeitos de furca; Plasma rico em plaquetas; Regeneração tecidual guiada; Membrana bioabsorvível